Resistance-breaking strains of tomato spotted wilt virus hamper photosynthesis and protein synthesis pathways in a virus accumulation-dependent manner in Sw5-carrying tomatoes - Maria Isabella Prigigallo; Ugo Picciotti; Giovanni Bubici (Scientific Reports)
Abstract Tomato spotted wilt virus (TSWV; Orthotospovirus tomatomaculae) is one of the major horticultural threats due to its worldwide distribution and broad host range. In Italy, TSWV is widely spread in tomato (Solanum lycopersicum) crops and causes severe yield losses. In the last decades, several tomato varieties carrying the Sw-5b gene for resistance to TSWV have been released. We investigated the interaction between Sw-5b-carrying tomatoes and Sw5-Resistance-Breaking (SRB) TSWV to elucidate the molecular mechanisms underlying resistance breakage. Transcriptome sequencing (RNA-Seq) was used to analyze 18 tomato leaf samples collected from a field crop naturally infected by SRB TSWV in Italy. An increase in virus accumulation level in leaf tissues (titer) resulted in a higher number of differentially expressed genes (DEGs), ranging from 33 to 44% of the whole transcriptome, when the samples with the lowest and the highest virus titer were compared to the asymptomatic sample, respectively. Photosynthesis and protein biosynthesis were the main down-regulated biological processes, while enzyme families such as oxidoreductases and transferases, genes related to the response to biotic stimuli, solute transport, and vesicle trafficking were overall up-regulated. Remarkably, the expression of around 45% of genes (ca. 14000) of the whole transcriptome was significantly (P < 0.05) correlated (positively or negatively) to the virus titer, and in 6% of cases (about 2000 genes) the correlation was high (i.e., absolute value of R2 > 0.85). This phenomenon was also verified on 15 genes by a quantitative reverse transcription PCR assay on a greenhouse experiment with a different Sw-5b-tomato variety artificially inoculated with another SRB TSWV strain. In conclusion, the tomato transcriptome was considerably rearranged upon TSWV infection, with deregulation of photosynthesis, protein biosynthesis, and induction of defense pathways. Finally, this research demonstrated that the magnitude of transcriptional changes was proportional to the virus accumulation level in the leaves.